Access to Public Health Services for the People in Ayutthaya Municipality - Bamrungsorn , Bo; Anusanpat , Narumon (Journal of Dhamma for Life, 2025)
The purposes of this research were to: 1) study level of access to public health services for the people in Ayutthaya Municipality; 2) compare access to public health services for the people in Ayutthaya Municipality classified by personal factors; and 3) presenting guidelines for access to public health services for the people in Ayutthaya Municipality. There were two research methods used in this study. The first stage was quantitative research. the sample group, obtained by stratified random sampling, consisted of 397 public health service recipients whose residence is registered in the population register in in Ayutthaya Municipality. The research instrument was a questionnaire of access to public health services for the people in Ayutthaya Municipality with a reliability level at 0.99. Statistical analysis was performed in terms of frequency, percentage, mean, standard deviation, t-test, one-way ANOVA, LSD test. The second stage was qualitative research. Key informants were 9 people, including executives, workers and service recipients, who were selected through purposive selection. The research instrument was a semi-structured interview and data was analyzed using content analysis techniques. The research findings revealed as follows: 1) the level of access to public health services of people in Ayutthaya Municipality is at a high level overall. The aspect with the highest average value is access to service sources, followed by the ability to pay for services, and the aspect with the lowest average value is the adequacy of available services; 2) Service recipients with different levels of education, occupations, monthly incomes, and length of stay in the community have different overall access to public health services in Phra Nakhon Si Ayutthaya Municipality, with statistical significance at the 0.05 level; and 3) The guidelines for access to public health services for people in Ayutthaya Municipality consist of 34 action items, divided into 5 areas: Sufficiency of existing services, consisting of 8 action items, such as promoting public health personnel with basic knowledge, such as village health volunteers (VHVs) or officers working in the area to receive additional training to develop skills and be able to assist in providing basic health services; Access to service sources, consisting of 5 action items, such as developing and promoting the use of telemedicine systems, which will help people access public health services more conveniently, allowing them to consult doctors and receive initial diagnoses from home, reducing restrictions on traveling to a hospital, and reducing time and costs, as well as being able to continuously monitor symptoms and receive medical advice; Convenience and facilities of service sources, consisting of 8 action items, such as using applications or digital platforms for making appointments in advance to reduce waiting times in hospitals; Affordability of paying for services, consisting of 6 action items, such as developing a primary health care network to make basic treatment easily accessible and economical; and Acceptability of service quality, consisting of 7 action items, such as providing complete and easy-to-understand information about services and benefits for people to access.